What is a Certified Hernia Center? The Example of the German Hernia Society and German Society of General and Visceral Surgery - Köckerling, Ferdinand; Berger, Dieter; Jost, Johannes O. (Frontiers in Surgery, 2014)
To date the scientific definition "Hernia Center" does not exist and this term is beeing used by hospitals and private institutions as a marketing instrument. Hernia surgery has become increasingly more complex over the pass 25 years. Differenciated use of the various techniques in hernia surgery has been adopted as a " taillord approach" program and requires intensive engagement with, and extensive experience of, the entire field of hernia surgery. Therefore there is a need for hernia centers. A basic requirement for a credible certification process for hernia centers involves definition of requirements and there verification by hernia societies and/or non-profit organizations that are interested in assuring the best possible quality of hernia surgery. At present there are two processes for certification of hernia centers by hernia societies or non-profit organizations.